2019
DOI: 10.1680/jcoma.16.00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acrylic latex on the properties of cement grouts

Abstract: The main objective of this comprehensive laboratory project was to investigate the potential use of acrylic latex to improve the physical and mechanical properties of thick superplasticised cement grouts. Experiments were conducted using different acrylic latex dosages with cement grouts that were prepared with water to cement ratios of 0·5, 0·4 and 0·33. The results indicated that the addition of acrylic latex of up to 5% significantly increases the 28 and 90 d strength, despite an extension of the setting ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
1
1
1
Order By: Relevance
“…The rheological behaviour of all the unmodified or acrylic resin-modified grouts (AMGs) was strongly shear thickening, and their apparent viscosity appeared to be enhanced with the increase in the applied pressure, as shown by the flow curves, irrespective of the AR content and the w/c ratio. This is consistent with the results reported in previous studies [35,[41][42][43]. As indicated by the experimental results, the addition of AR to some extent modifies the rheological properties of all grouts, which appeared to be slightly more or less viscous in comparison to the unmodified grouts.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The rheological behaviour of all the unmodified or acrylic resin-modified grouts (AMGs) was strongly shear thickening, and their apparent viscosity appeared to be enhanced with the increase in the applied pressure, as shown by the flow curves, irrespective of the AR content and the w/c ratio. This is consistent with the results reported in previous studies [35,[41][42][43]. As indicated by the experimental results, the addition of AR to some extent modifies the rheological properties of all grouts, which appeared to be slightly more or less viscous in comparison to the unmodified grouts.…”
Section: Resultssupporting
confidence: 92%
“…Bleeding was more pronounced in the case of ER and for the thinner grouts. These results contradict previous research findings [43,61], which concluded that, generally, the volume loss of the modified system is reduced after the addition of polymers. Obviously, the addition of high dosages of polymer (especially ER) and PCE superplasticiser increases the dispersion ability, so the cement mixture entraps less water and, consequently, results in the reduction of the final volume [63].…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation